2021
DOI: 10.1097/hjh.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

The aortic-femoral arterial stiffness gradient: an atherosclerosis risk in communities (ARIC) study

Abstract: The aortic to femoral arterial stiffness gradient (af-SG) may be a novel measure of arterial health and cardiovascular disease (CVD) risk, but its association with CVD risk factors and CVD status, and whether or not they differ from the referent measure, carotid-femoral pulse-wave velocity (cfPWV), is not known. Accordingly, we compared the associations of the af-SG and cfPWV with,(1) age and traditional CVD risk factors, and (2) CVD status. We evaluated 4,183 older-aged (75.2±5.0 years) men and women in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Finally, it has been suggested that loss of elasticity and recoil may not necessarily translate to arterial stiffening, and may occur in the absence of stenosis [52]. But whether through atherosclerotic-dependent or -independent means, low faPWV may contribute to a reduction in the central to peripheral arterial stiffness gradient, augmenting the transmission of excessive forward pressure into the microcirculation, a pathophysiological basis for cardiovascular events and target organ damage [53,54].…”
Section: Comparison To the Literature: Prevalent Cvdmentioning
confidence: 99%
“…Finally, it has been suggested that loss of elasticity and recoil may not necessarily translate to arterial stiffening, and may occur in the absence of stenosis [52]. But whether through atherosclerotic-dependent or -independent means, low faPWV may contribute to a reduction in the central to peripheral arterial stiffness gradient, augmenting the transmission of excessive forward pressure into the microcirculation, a pathophysiological basis for cardiovascular events and target organ damage [53,54].…”
Section: Comparison To the Literature: Prevalent Cvdmentioning
confidence: 99%
“…In the ARIC study population, a cross-sectional analysis showed that a low arterial stiffness gradient (femoral-ankle PWV/cf-PWV) was associated with diabetes, coronary heart disease, heart failure, and stroke, whereas a high cf-PWV was only associated with hypertension ( Stone et al, 2021 ). It should be mentioned that this is a relatively older cohort (age of 75 years) with a higher prevalence of hypertension (72%) and diabetes (29%).…”
Section: Discussionmentioning
confidence: 99%
“…By the study in aortic aging, the importance of "normal" stiffness gradient has been recently come to light. Agerelated increase in aortic stiffness causes the loss of stiffness gradient and results in increasing forward wave amplitude and pulse pressure (Figure 4B) (43). The loss of stiffness gradient leads to the transmission of a highly pulsatile pressure wave into the microcirculation (44).…”
Section: Regional Pwv In Patients With Chdmentioning
confidence: 99%